2012
DOI: 10.1111/j.1462-2920.2012.02852.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic distribution of traits associated with plant colonization in Escherichia coli

Abstract: Plants are increasingly considered as secondary reservoirs for commensal and pathogenic Escherichia coli strains, but the ecological and functional factors involved in this association are not clear. To address this question, we undertook a comparative approach combining phenotypic and phylogenetic analyses of E. coli isolates from crops and mammalian hosts. Phenotypic profiling revealed significant differences according to the source of isolation. Notably, isolates from plants displayed higher biofilm and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
90
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 74 publications
(112 reference statements)
10
90
1
Order By: Relevance
“…Generally, commensal enteric strains belong to phylogenetic groups A and B l, whereas extraintestinal pathogenic strains are placed into group B2 and, to a lesser extent, group D (10,20,21,40). Our findings are consistent with those of Meric et al (31), who recently reported a higher prevalence of Bl isolates on plants than isolates of other phylogenetic groups. B l strains have been recovered from a wide variety of sources (e.g., humans, livestock, natural environments), and thus they are considered to be host generalists (6,48).…”
Section: Resultssupporting
confidence: 95%
“…Generally, commensal enteric strains belong to phylogenetic groups A and B l, whereas extraintestinal pathogenic strains are placed into group B2 and, to a lesser extent, group D (10,20,21,40). Our findings are consistent with those of Meric et al (31), who recently reported a higher prevalence of Bl isolates on plants than isolates of other phylogenetic groups. B l strains have been recovered from a wide variety of sources (e.g., humans, livestock, natural environments), and thus they are considered to be host generalists (6,48).…”
Section: Resultssupporting
confidence: 95%
“…These results were consistent with recent studies showing that E. coli B1 strains can persist longer in water than strains of the other phylogroups (13,14). The prevalence of B1 isolates has also been observed in other environmental samples, such as manure and drinking water, or associated with plant colonization (see the reference list in reference 43).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the ability to utilize sucrose could provide a substantial advantage in the environment (43,45). However, in this study, no relationship between carbon degradation and the survival ability of isolates was observed.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Thus, the plant rhizosphere, already known for its ability to host populations known to be human pathogenic and belonging to P. aeruginosa (75,76), Burkholderia spp. (77,78), or Escherichia coli (79), could also be a potential source of P. fluorescens opportunistic pathogens. The possible involvement of Hrp1 family secretion systems in the virulence of respiratory tract isolates toward animal cells is supported by the altered virulence of a mutant of the respiratory tract isolate P. fluorescens MFN1032 (syn.…”
Section: Discussionmentioning
confidence: 99%